Coexistence and peace based on diversity in a multicultural society: Case study of ban rai community, Soppong sub-districy, Pang Mapha district Mae Hong Son province - Sanmee, Wichian; Pharcharuen, Winit; Uthaphan, Phattharachai; Phutchu, Surachai; Thongputtamon, Notnargorn (Linguistics and Culture Review, 2021)
This research paper is qualitative research, and the objectives are as follows: 1) To study the context of the community and society Political Culture and economy that facilitate coexistence 2) To study the factors contributing to coexistence and peace based on diversity in a multicultural society. Data was collected by gathering them from relevant documents, In-depth interviews with informants, small group chat, and participatory observation. The groups that provide information consists of community leaders, religious leaders, ethnic leader’s expert and the villagers, totalling 39 people. The researcher found out that: The social community context has strong relationships between networks. In terms of governance, there is a decentralized government to divide the government into a community worthwhile. Common village rules in terms of culture, beliefs, traditions, and rituals are inherited from ancestors and economic aspects, the concept of sufficiency economy is applied to the practice of integrated agriculture. It leads to the integration and formation of groups for the production, distribution, fundraising within the community. This is an important mechanism to ensure the sustainability of a shared learning community.